Role of two-stage strike slip faulting in the tectonic evolution of the Doseo depression in the central Africa rift system - Zhang, Xinshun; Dou, Lirong; Nie, Zhiquan; Xiao, Kunye; Wang, Lin; Du, Yebo; Chen, Shi; Wang, Li; Zhou, Xiaorong (Frontiers in Earth Science, 2023)
Doseo depression of Central African Rift System is an important onshore frontier area for oil and gas exploration in Africa, with rift development characterized by the dual control of fault-depression development and strike slip faulting. According to the latest drilling and seismic data in recent years, through the fine seismic interpretation, the calculation of paleo-fault throw and fault growth index and the method of balanced profile cross-section restorations, the fault characteristics and tectonic setting of Doseo depression are analyzed in detail, especially the fault activity, tectonic evolution and genetic mechanism of two large-scale strike slip movements in Doseo depression. The results show that the Doseo depression experienced five main tectonic phases, including two stages of strike slip tectonic movements with different mechanisms. The first stage is characterized by strike slip tectonic movements under tilting extension, which controls the overall structure of the depression. The second stage is characterized by strike slip tectonic movements under transform compression, which play an important role in the formation of some inversion structures and SW-NE trending anticlines and faulted anticlines. The superposition of an early faulted-depression and two later stages of strike slip tectonics led to current pattern of Doseo depression.